Interaction Between MDSC and NK Cells in Solid and Hematological Malignancies: Impact on HSCT - Tumino, Nicola; Di Pace, Anna Laura; Besi, Francesca; Quatrini, Linda; Vacca, Paola; Moretta, Lorenzo (Frontiers in Immunology, 2021)
Myeloid derived suppressor cells (MDSC) are heterogeneous populations that through the release of soluble factors and/or by cell-to-cell interactions suppress both innate and adaptive immune effector cells. In pathological conditions, characterized by the presence of inflammation, a partial block in the differentiation potential of myeloid precursors causes an accumulation of these immunosuppressive cell subsets both in peripheral blood and in tissues. On the contrary, NK cells represent a major player of innate immunity able to counteract tumor growth. The anti-tumor activity of NK cells is primarily related to their cytolytic potential and to the secretion of soluble factors or cytokines that may act on tumors either directly or indirectly upon the recruitment of other cell types. NK cells have been shown to play a fundamental role in haploidentical hemopoietic stem cell transplantation (HSCT), for the therapy of high-risk leukemias. A deeper analysis of MDSC functional effects demonstrated that these cells are capable, through several mechanisms, to reduce the potent GvL activity exerted by NK cells. It is conceivable that, in this transplantation setting, the MDSC-removal or -inactivation may represent a promising strategy to restore the anti-leukemia effect mediated by NK cells. Thus, a better knowledge of the cellular interactions occurring in the tumor microenvironment could promote the development of novel therapeutic strategies for the treatment of solid and hematological malignances.